Historicizing the Religious Field: Adapting Theories of the Religious Field for the Study of Medieval and Early Modern Europe - Steckel, Sita (Church history and religious culture, 2019)
As historians of religion are currently diagnosing a need to find new shared frameworks and new narratives enabling interdisciplinary and trans-epochal exchange, the article suggests a closer historical engagement with theories of the "religious field", originally formulated by Pierre Bourdieu on the basis of Max Weber's work, as this theory has the potential to serve as a meta-language for interdisciplinary communication. The article sets out the most important elements of the theory of the religious field, and evaluates them critically by way of a historicization of important concepts, drawing on recent discussions in sociology and Religious Studies. After discussing the concept of the religious field itself, the article discusses several internal dynamics of the field (as suggested by Bourdieu and by more recent research) as well as several typical dynamics between fields. It concludes with suggestions for historical adaptations, including an updated approach to religious plurality and to the different types of religious actors envisaged by Weber and Bourdieu.